The Tribological Study On Polymer Matrix Composite Using Pin On Disc Testing Technique - Mohd Fathi Bin Ismail, Mohd Fathi (Universiti Teknologi Petronas, 2010)
A polymer is generally manufactured by polycondensation, polymerization or polyaddition, when combined with various agents to enhance or in any way alter the material properties of polymers the result is referred to as a plastic [1,2]. Composite plastics refer to those types of plastics that result from bonding two or more homogeneous materials with different material properties to derive a final product with certain desired material and mechanical properties. Advanced polymer composites are generally understood to be materials consisting of a polymer matrix reinforced with high-strength continuous fibers of a predefined orientation.